2018
DOI: 10.3390/met8080581
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemical Composition in Corrosion of Aluminum Alloys

Abstract: Aluminum alloys are the most important part of all shaped castings manufactured, especially in the aerospace and automotive industries. This work focuses on the corrosion properties of the heat-hardening aluminum alloys commonly used for production of automotive castings AlSi7Mg0.3 and on self-hardening AlZn10Si8Mg. Iron is a common impurity in aluminum cast alloy and its content increases by using secondary aluminum alloys. Therefore, experimental materials were developed, with chemical composition according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 31 publications
0
27
0
2
Order By: Relevance
“…It should be taken into account that the pitting corrosion attack is related to the locale surface imperfections and therefore the corrosion rate cannot be the substantial factor in the evaluation of the local corrosion resistance [19,20,24]. As can be considered from Table 5 there is marked difference between the average corrosion rate of the as received specimens and the electropolished ones.…”
Section: Exposure Immersion Testmentioning
confidence: 99%
“…It should be taken into account that the pitting corrosion attack is related to the locale surface imperfections and therefore the corrosion rate cannot be the substantial factor in the evaluation of the local corrosion resistance [19,20,24]. As can be considered from Table 5 there is marked difference between the average corrosion rate of the as received specimens and the electropolished ones.…”
Section: Exposure Immersion Testmentioning
confidence: 99%
“…Alloy 2 (AlSi12CuNiMg) could additionally form the phases: ε–Al 3 Ni, γ–Al 7 Cu 4 Ni, δ–Al 3 CuNi(Al 3 Ni 2 ), T–Al 9 FeNi [41] and α–Al 11 (MnFeNiCu) 4 Si [58]. In [59] it is suggested that some intermetallic play an active role in the resistance to corrosion: intermetallic particles such as the Al 2 CuMg and Mg 2 Si show anodic behaviour acting as preferential corrosion site while intermetallic phases such as Al 2 Cu, AlFeMnSi, AlCuFeMn, AlCuFeSi, show cathodic behaviour causing the corrosion of the surrounding α–Al matrix. Because of the contemporary presence of several different intermetallic phases, the eutectic alloy (alloy 2) is less corrosion resistant than the hypoeutectic alloy (alloy 1).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, in industrial cast aluminum alloys manganese is contained in an amount of up to 0.5 % wt., and for wrought -up to 1 % wt. [1,3,11,17,18]. Like copper, manganese forms a eutectic with aluminum, but at a higher temperature.…”
Section: нові литі матеріалиmentioning
confidence: 99%
“…by 657 0 C [3]. The solubility of manganese in aluminum at the temperature of eutectic transformation is about 1.8 % wt., and at room temperature -0.168 % wt., so it could be considered as an effective reinforcing element [3,6,10,18]. The strengthening phase is Al 6 Mn, which is released from the supersaturated solid solution during age-hardening.…”
Section: нові литі матеріалиmentioning
confidence: 99%